Advances in agronomy: Vol.53 (Academic, 1994)
The book consists of four chapters. The first chapter comprehensively reviews the history of crop rotations and future directions in this important area. The second chapter provides a thorough discussion on how dissolution and precipitation affect soluble aluminum in acid soils. The third chapter presents the role that nutrient management has on optimal water. The fourth chapter is a definitive treatise on how interparticle forces, soil water relations, swelling of clays, surface area and pore size, water stability od soil aggregates, and sodic soils